Caracterização do perfil de resposta inflamatória periapical frente às infecções de origem endodôntica em pacientes portadores de Diabetes Mellitus Tipo II em uso de Metformina - Gabriel Ferreira Pessoa Carvalho Miranda (2019)
Introduction: Systemic diseases are known to cause repercussions on oral diseases. Diabetes Mellitus (DM) is an endocrine disorder with a significant world incidence. The association between DM and endodontic apical periodontitis (AP) has not been clearly determined. This paper aims to analyse the immune profile during periapical infections of endodontic origin in patients with type II DM. Methodology: Bacterial and periapical fluid samples were collected from 12 patients presenting type II DM and 12 non-diabetic patients, all in need for endodontic therapy due to the presence of pulp necrosis. Diagnosis was based on clinical and radiographic analyses and pulp sensibility testing. The following cytokines and chemokines were analyzed by real-time PCR: IL-1-β, IL-6, IL-10, IL-17A, IFN-γ, TNF, CCL2, CCR6, CCL4, CXCR4, as well as mRNA 16S gene expression. Results: Gene expressions of mRNA for 16S, IL10 and IL6 were similar between both groups; mRNA for IL-1-β and CXCR4 were higher in diabetic than in non-diabetic subjects, whereas TNF, IFN- γ, IL17A, MCP1, CCR6 and CCL4 were lower in diabetic subjects. Conclusion: Type II DM individuals present different expression of cytokines and chemokines in the periapical tissue in response to root canal infections than that of non-diabetic patients. In addition, it seems that metformin impacts the overall immune response, down-regulating pro-inflammatory mediators, such as TNF and IFN-γ, even in the presence of infection inside the root canal system.